On Himalaya clauses, bailments, choice of law and jurisdiction: Recent Privy Council perspectives from The Mahkutai - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 1996)
Decision in The Mahkutai case - drafting and construction of Himalaya clauses - bailment on terms - Himalaya clause as evidence of consent - scope of bailment on terms after The Mahkutai